High prevalence of metabolic syndrome and insulin resistance in adolescents receiving chemotherapy for acute lymphoblastic leukemia - Purnamasari, Dian Hadi; Widjaja, Nur Aisiyah; Andarsini, Mia Ratwita (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Acute lymphoblastic leukemia (ALL) is a common pediatric cancer with improved survival rates due to advancements in chemotherapy. However, survivors face an elevated risk of metabolic disorders, including insulin resistance and metabolic syndrome. This study aimed to assess the prevalence of insulin resistance and metabolic syndrome in overweight and obese adolescents undergoing maintenance chemotherapy for ALL, compared to a control group without ALL.Methods: An observational case-control study was conducted involving 45 adolescents, with 9 in the case group (overweight and obese adolescents with ALL) and 36 in the control group (overweight and obese adolescents without ALL). Insulin resistance was assessed using the HOMA-IR, and metabolic syndrome was diagnosed based on the IDF criteria. The statistical analysis included independent-sample t-tests, chi-square tests, and logistic regression.Results: The prevalence of insulin resistance was significantly higher in the case group compared to the control group (88.9% vs. 47.2%, P < 0.05), with a mean HOMA-IR score of 5.94 ± 3.98 in the case group and 2.73 ± 1.20 in the control group. Metabolic syndrome prevalence was also higher in the case group (66.7% vs. 22.2%, P < 0.05). Adolescents with ALL had a 10-fold increased risk of developing insulin resistance and metabolic syndrome simultaneously (OR: 10, P < 0.05).Conclusions: Overweight and obese adolescents undergoing chemotherapy for ALL were at significantly higher risk of insulin resistance and metabolic syndrome. Early screening and intervention during chemotherapy are essential to mitigate long-term metabolic risks and improve overall outcomes. (www.actabiomedica.it)